2011
DOI: 10.1007/s11255-011-9984-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of insulin resistance with arterial stiffness in nondiabetic peritoneal dialysis patients

Abstract: Insulin resistance is an independent risk factor for arterial stiffness in PD patients older than 50 years. IR is not associated with carotid intima-media thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…In a larger-scale epidemiological study, insulin resistance was significantly more frequent in PD patients than in hemodialysis and pre-dialysis subjects (47 vs. 21 and 26 %, respectively) [ 28 ]. In a study by Tatar et al [ 29 ], insulin resistance was an independent risk factor for arterial stiffness in nondiabetic PD patients older than 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a larger-scale epidemiological study, insulin resistance was significantly more frequent in PD patients than in hemodialysis and pre-dialysis subjects (47 vs. 21 and 26 %, respectively) [ 28 ]. In a study by Tatar et al [ 29 ], insulin resistance was an independent risk factor for arterial stiffness in nondiabetic PD patients older than 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al showed a positive relationship between the insulin levels and carotid stiffness in 80 nondiabetic CKD patients 84) . In a more recent article, we demonstrated that insulin resistance is a risk factor for cardiovascular disease in nondiabetic patients older than 50 years of age 41) . Of the 53 patients enrolled in that study, 48 were on continuous ambulatory peritoneal dialysis (PD) and five were on automated PD.…”
Section: Insulinmentioning
confidence: 95%
“…CKD is associated with decreased insulin degradation and insulin resistance (IR) at the postreceptor level, leading to hyperinsulinemia. The complex interplay between metabolic abnormalities, such as vitamin D deficiency, obesity, metabolic acidosis, inflammation and the accumulation of "uremic toxins," is believed to contribute to the etiology of IR in CKD patients 41) . Disturbed insulin metabolism and increased insulin resistance are well-known contributors to morbidity in mortality in both the general and CKD population [42][43][44] .…”
Section: Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two studies investigated the association between insulin resistance and cardiovascular morbidity in PD patients (9,10). Tatar et al showed that insulin resistance was an independent risk factor for arterial stiffness as indicated by carotid-femoral pulse wave velocity (9). Sevinc Ok et al suggested that high glucose exposure from dialysis solution was a risk factor for vascular calcification (10).…”
mentioning
confidence: 99%